Equine arteritis virus cytopathic effect: caspase-dependent cell death as the major consequence observed - Abeyá, María Mercedes (2018)
Equine arteritis virus infection in horse populations could be confirmed by the OIE recommended Virus Neutralization (VN) test and by the gold standard Virus Isolation (VI). These two techniques involve the observation of the cytopathic effect (CPE) of EAV. The characteristic CPE in EAV infections is the cellular lysis. The presence/ absence of this CPE in cells in the VI/VN respectively, indicate the positivity of each test. CPE refers to morphological and molecular changes that where evidence in infect cells after viral infections. Most viral infections eventually result in the death of the host cell by different cellular mechanisms. The causes of death include cell lysis by alterations to the cell’s surface membrane and by various modes of programmed cell death such as necrosis, apoptosis, autophagy and others. EAV CPE is always refers as cellular lysis but the mechanism involve in this lytical effect has never specifically determined. So, our objective is to extend the concept of the cytopathic effect of EAV infections. To study the effect of different cell death mechanism in EAV CPE we used different inhibitors. Consequently, we concluded that the most important mechanism of cell death in EAV infections is caspase-dependent cell death.